IS-RPB-intensified resource utilization of coal fly ash coupled with multidimensional techno-economic and life cycle assessment - Zhiguo Yuan; Zhong Guo; Chunge Dang; Shuli Zhang; Youzhi Liu; Ruichen Wang (Process Safety and Environmental Protection, 2026)

A review of lithium extraction from primary and secondary lithium resources using supercritical CO2 - Hongquan Wei; Jie Liu; Ruichen Wang; Yanjun Li; Yuexin Han; Chengxiu Li (Hydrometallurgy, 2026)

Engineering orbital coupling in rare-earth-doped layered double hydroxides for enhanced wound healing - Jiajia Jing; Yan Miao; Xiaotong Ma; Ruichen Wang; Haojie Wei; Chuxuan Liu; Kelong Fan; Jingping Zhong; Haifeng Liu (Chemical Engineering Journal, 2026)

High entropy alloy PtRuCuCoNi nanosponges with tunable electronic configurations for electrocatalytic lactic acid oxidation toward upcycling waste polylactic acid - Bingshuo Li; Xiaokun Fa; Ruichen Geng; Liuyang Jiang; Ruiping Liu; Zhihan Zhang; Yinglong Wang; Shuli Yin (Chemical Engineering Journal, 2026)

Tuning surface residual lithium into a Li-ion-conductive protective interphase toward stable Ni-rich cathodes - Shumin Liu; Huangzhang Zhou; Wenhao Jia; Yingjie Sun; Peng Gao; Ruichen Zhu; Yongming Zhu; Xudong Li; Liguang Wang (Chemical Engineering Journal, 2026)

Succession patterns, environmental connections, and assembly mechanisms of gut microbiota in the giant freshwater prawn (Macrobrachium rosenbergii) across lifespan - Songbao Zou; Yao Zheng; Julin Yuan; Meng Ni; Mei Liu; Dan Zhou; Qiang Gao; Mingfeng Deng; Ruichen Wang; Xin Zhang (Aquaculture, 2026)

Postharvest application of plasma-activated water delays anthracnose symptom development in apples - Yingman Gao; Ruichen Sha; Guihuan Wei; Lingling Yang; Yupan Zhu; Yudong Liu; Ruonan Ma; Zhen Jiao; Bing Li (Postharvest Biology and Technology, 2025)

In situ growth of ultrasmall MoO3 nanoparticles into 3D porous reduced graphene oxide for efficient oxidative desulfurization of high-sulfur - Peng Zuo; Xianping Chu; Fanfan Liu; Xu Cai; Ruichen Li; Yanbo Sun; Zhouqin Xu; Zhiwei Zhang; Yun Shen; Jinyun Liu; Yefeng Liu (Journal of Environmental Chemical Engineering, 2025)

Upcycling PET waste into carbon quantum dots as flame retardant of PET for closed-loop recycling - Jianfei Wei; Guocong Ma; Yaoyao Tang; Jing Zhang; Gaoling Jin; Chaohui Ma; Linhan Bing; Zhiguo Zhu; Zhenfeng Dong; Puzhen He; Ruichen Zhou; Rui Wang; et al. (Chemical Engineering Journal, 2025)

Discovering VEGFR-targeting constituents from Chloranthus holostegius guided by affinity screening - Wenhui Liu; Haojing Jiang; Xinxing Li; Ruichen Guo; Jing Xu; Yuanqiang Guo (Phytochemistry, 2025)

Global sustainable pathway for lithium metal production: A critical review and best practice guide - Ruichen Wang; Yuexin Han; Yanjun Li; Feilong Zhang; Chunge Dang; Zhiguo Yuan; Jie Liu (Chemical Engineering Journal, 2025)

Self-templated fabrication of heterogeneous F doped NiCo-alkoxides/NiCo hydroxides yolk-shelled spheres with enhanced performance for supercapacitors - Xu Zhang; Ying Chen; Shuxian Song; Lu Song; Ruichen Zhai; Yulan Meng; Shaojie Li; Lijuan Wei; Xutong Yang; Anmin Liu (Chemical Engineering Journal, 2025)

Engineering the primary and second coordination sphere of metal-organic framework boosts the peroxidase-like activity - Xin Yuan; Xinghua Chen; Jun Xiong; Yifang Cao; Niya Ta; Ruichen Gao; Shuli Liu; Min-Hua Zong; Xiaoling Wu; Wen-Yong Lou (Chemical Engineering Journal, 2025)

Development of a novel targeted LC-MS/MS methods for the typing of cardiac amyloidosis - Kaijuan Wang; Ruichen Liu; Li Li; Xuejing Duan; Xianglong Zhao; Hongying Cong; Xiaojing Gao; Kunlun Yin; Zhangwei Gao; Zhou Zhou (Analytica Chimica Acta, 2025)

Serum polychlorinated biphenyls as a risk factor for MASLD: Exploring the association and underlying mechanisms - Ruichen Yang; Qingqing Jiang; Wentao Liu; Furong Wang; Shiyi Cao (Science of The Total Environment, 2025)

Oil Spill Occurrence and Pollution Risk Assessment Based on Sea State, Oil Platform Location, and Shipping Route Density in the Bohai Sea - Tao Liu; Ruichen Cao; Minxia Zhang; Xing Chen; Fan Bi; Jiangling Xu (Journal of Marine Science and Engineering, 2025)
The Bohai Sea is the only semi-enclosed inland sea in China. With active marine economic activities, it faces a persistently high risk of oil spill accidents. This study assesses the occurrence risk and pollution risk of oil spills by considering factors such as sea state, the location of oil platform, and shipping route density in the Bohai Sea. The results show that the central part of the Bohai Sea, the southern Liaodong Peninsula, and the Bohai Strait area have a relatively high occurrence risk of oil spills due to busy maritime traffic and harsh sea conditions. In contrast, some areas in the northern, western, and southern parts of the Bohai Sea have a relatively low occurrence risk of oil spills because of weak maritime activity intensity and relatively calm sea state. In terms of the oil pollution risk, its distribution in the Bohai Sea shows significant seasonal characteristics, which are mainly comprehensively affected by multiple dynamic factors such as circulation, monsoon, and seawater exchange. Based on the oil pollution risk distribution, seasonally targeted strategies are proposed, which can provide a scientific basis for oil spill prevention and emergency management in the Bohai Sea, and help relevant departments formulate targeted prevention and control strategies.

Rice cultivation and its environmental and social contexts at the Shimao site, Northwest China - Shu Liu; Ruichen Yang; Zhouyong Sun; Jing Shao; Zhikun Ma (Archaeological and Anthropological Sciences, 2025)

Ecological and Evolutionary Factors Contribute to the Uneven Diversification of Firs in the Northern Hemisphere - Qiaoping Xiang; Jie Yang; David S. Gernandt; Tongxin Ye; Ling Yang; Jiaming Pan; Ruichen Xiang; Cheng Zhao; Koh Nakamura; Xianchun Zhang; Yongbo Liu; Ran Wei (Journal of Biogeography, 2025)
Aim The Northern Hemisphere harbours the greatest diversity of temperate plants on Earth, with East Asia having the highest species richness compared with North America and Europe. When and how this uneven diversification pattern emerged remains unclear. Here, we use a conifer genus that forms extensive forests in the Northern Hemisphere to explore a fundamental question in ecology and evolution: what processes underlie temperate biodiversity through time and space? Location The Northern Hemisphere. Taxon Abies . Methods To reconstruct a well‐supported framework for estimating diversification rate, we performed phylogenetic analyses using concatenation and coalescent methods based on 58 fir taxa and 56 nuclear single‐copy genes. Niche evolution was explored using species occurrence data and environmental factors based on the l1ou model. Multiple regression was carried out to identify correlations between species richness and environmental variables at global and regional scales, to evaluate factors of species diversity preference, and potentially to explain the evolutionary history of firs. Results We identified East Asia as having the highest species diversity and speciation rate. Two clade‐specific niche shifts corresponding with the distribution of firs were detected, one in the Himalaya‐Hengduan Mountains ( c. 12.2 Ma) and the other in the Mexican highlands ( c. 14.3 Ma), but none in the Euro‐Mediterranean region. Fir species richness increased with cool temperatures both globally and regionally. Seasonal precipitation showed significant positive correlation to species richness on a global scale and in North America and the Euro‐Mediterranean region. Soil factors showed significant trends and moderate correlations with species richness in the Himalaya‐Hengduan Mountains and Mexican highlands. Main Conclusions Our results indicate that modern firs prefer cool climates with seasonal rainfall. East Asian firs experienced niche shifts with the Himalayan orogeny in the Middle Miocene. Novel heterogeneous habitats due to changes in topography and the establishment of a monsoon climate, accompanied by niche shift, can account for the high speciation of firs in East Asia. A similar process is found in the Mexican highland firs. In contrast, cold–dry continental climate in North America since the late Paleogene and the lack of seasonal rainfall and relatively stable topography in the Euro‐Mediterranean region are the main limiting factors for fir diversification. Our study rejects the ‘clade age’ hypothesis but supports the hypothesis that niche shift related to high diversification rate triggered by environmental heterogeneity underlies the uneven species diversity of the Northern Hemisphere.

Techno-economic-environmental analysis based on life cycle carbon accounting and pollutants audit for cleaner production of electrolytic manganese - Ruichen Wang; Shuli Zhang; Yajing Guo; Jingyang Liu; Feilong Zhang; Chunge Dang (Process Safety and Environmental Protection, 2024)

Genomic selection on ear height, plant height and grain yield in the primary testing stage of maize hybrids - Xinying Kong; Shuwen Ji; Yubo Liu; Xuecai Zhang; Meiling Liu; Chen Yue; Ruichen Yang; Cong Li; Xiaomei Dong; Ao Zhang; Yanye Ruan (Euphytica, 2024)

Research on scallop shells transport of the Yantai coastal region in the Bohai Sea - Le Chen; Yibo Zhang; Yongzhi Liu; Ruichen Cao; Xianqing Lv (Frontiers in Marine Science, 2024)
Introduction Bivalve aquaculture is an important pillar of China's fisheries, with over 1 million tonnes of scallop shells produced annually. However, most of these shells are directly discarded into the sea, leading to continuous pollution of the marine and coastal environments, especially the coast of Yantai in the Bohai Sea where a large number of discarded scallop shell have accumulated. Methods To trace the fate of scallop shells in the ocean, this study established a model for the transport of scallop shells, coupling a two-dimensional tidal current model using the adjoint method with a Lagrangian particle model. By simulating nested tidal models, the distribution of tidal residual current in the Yantai coastal region was obtained. Then, a Lagrangian particle model was used to track the transport pathways of pollutants in the sea. Results Driven by the residual current calculated from the tidal model with the actual situation, possible pollutant release areas were inferred. The results of Lagrangian particle tracking experiments indicate that pollutants were released from the upstream accumulation area, specifically the area near Penglai Hulushan, confirming previous speculation. Discussion The scallop shells transport model can accurately simulate the spatiotemporal profile of scallop shells, which is helpful for managing scallop shell resources and improving the level of shell reuse.

InSAR-derived predisaster spatio-temporal evolution of a reactivated landslide - Kun He; Gang Luo; Chuanjie Xi; Bo Liu; Xiewen Hu; Ruichen Zhou (Bulletin of Engineering Geology and the Environment, 2024)

Insectivorous birds are more sensitive to urban greenspace changes in Guangzhou city, China - Ruichen Wu; Qiang Zhang; Zezhou Hao; Le Li; Bingtao Gao; Jianrong Li; Xiaotian Liu; Chao Liao; Nancai Pei (Urban Forestry & Urban Greening, 2024)

DEHP and DBP, common phthalates, induce glucose metabolism disorders in rats via oxidative damage of PI3K/Akt/GLUT4 signaling - Liping Li; Lingyan Huang; Ruichen Lei; Pengju Zhang; Yi Yang; Herong Liu; Yuhong Zhang (Environmental Pollution, 2024)

Modeling the long-term transport and fate of oil spilled from the 2021 A Symphony tanker collision in the Yellow Sea, China: Reliability of the stochastic simulation - Ruichen Cao; Zengrui Rong; Haibo Chen; Yi Liu; Lin Mu; Xianqing Lv (Ocean Modelling, 2023)

Dynamic characteristics and erosion effect of a landslide-induced debris flow which occurred in Pingwu, southwest China - Bo Liu; Kun He; Xiewen Hu; Yufang Zhang; Kun Yuan; Jian Cui; Chuanjie Xi; Ruichen Zhou (Bulletin of Engineering Geology and the Environment, 2023)

A Floating-Waste-Detection Method for Unmanned Surface Vehicle Based on Feature Fusion and Enhancement - Yong Li; Ruichen Wang; Dongxu Gao; Zhiyong Liu (Journal of Marine Science and Engineering, 2023)
Unmanned surface vehicle (USV)-based floating-waste detection presents significant challenges. Due to the water surface’s high reflectivity, there are often light spots and reflections in images captured by USVs. Furthermore, floating waste often consists of numerous small objects that prove difficult to detect, posing a robustness challenge for object-detection networks. To address these issues, we introduce a new dataset collected by USV, FloatingWaste-I, which accounts for the effects of light in various weather conditions, including sunny, cloudy, rainy and nighttime scenarios. This dataset comprises two types of waste: bottles and cartons. We also propose the innovative floating-waste-detection network, YOLO-Float, which incorporates a low-level representation-enhancement module and an attentional-fusion module. The former boosts the network’s low-level representation capability while the latter fuses the highest- and lowest-resolution feature map to improve the model robustness. We evaluated our method by using both the public dataset FloW-img and our FloatingWaste-I dataset. The results confirm YOLO-Float’s effectiveness, with an AP of 44.2% on the FloW-img dataset, surpassing the existing YOLOR, YOLOX and YOLOv7 by 3.2%, 2.7% and 3.4%, respectively.

Efficient predictor of pressurized water reactor safety parameters by topological information embedded convolutional neural network - Muzhou Hou; Wanjie Lv; Menglin Kong; Ruichen Li; Zhengguang Liu; Dongdong Wang; Jia Wang; Yinghao Chen (Annals of Nuclear Energy, 2023)

MPM-based mechanism and runout analysis of a compound reactivated landslide - Kun He; Chuanjie Xi; Bo Liu; Xiewen Hu; Gang Luo; Guotao Ma; Ruichen Zhou (Computers and Geotechnics, 2023)

Exogenous bile acids regulate energy metabolism and improve the health condition of farmed fish - Lei Wang; Gladstone Sagada; Chenyang Wang; Ruichen Liu; Qiang Li; Chen Zhang; Yunzhi Yan (Aquaculture, 2023)

Secotrijugins A−D, four highly oxidized and rearranged limonoids from Trichilia sinensis and their anti-inflammatory activity - Honghong Xing; Ziteng Song; Ruichen Guo; Feng Liu; Lijun An; Yuanqiang Guo; Ping Hu (Phytochemistry, 2023)

Pinocembrin Inhibits P2X4 Receptor–Mediated Pyroptosis in Hippocampus to Alleviate the Behaviours of Chronic Pain and Depression Comorbidity in Rats - Runan Yang; Jingjian Yang; Zijing Li; Ruichen Su; Lifang Zou; Lin Li; Xiumei Xu; Guilin Li; Shuangmei Liu; Shangdong Liang; Changshui Xu (Molecular Neurobiology, 2022)

Rapid Characterization of Landslide-Debris Flow Chains of Geologic Hazards Using Multi-method Investigation: Case Study of the Tiejiangwan LDC - Kun He; Bo Liu; Xiewen Hu; Ruichen Zhou; Chuanjie Xi; Guotao Ma; Mei Han; You Li; Gang Luo (Rock Mechanics and Rock Engineering, 2022)

Correction to: Preliminary analyses of the Tiejiangwan landslide occurred on April 5, 2021 in Hongya County, Sichuan Province, China - Bo Liu; Xiewen Hu; Kun He; Gen Li; Xin Liu; Gang Luo; Chuanjie Xi; Ruichen Zhou (Landslides, 2022)

Preliminary analyses of the Tiejiangwan landslide occurred on April 5, 2021 in Hongya County, Sichuan Province, China - Bo Liu; Xiewen Hu; Kun He; Gen Li; Xin Liu; Gang Luo; Chuanjie Xi; Ruichen Zhou (Landslides, 2022)

Prevention of acetaminophen-induced hepatocyte injury: JNK inhibition and GSTA1 involvement - Yicong Chang; Jingshan He; Bingke Ma; Muhammad Ishfaq; Jiaqi Wang; Ruichen Zhang; Liang Yuan; Jiarui Liu; Changwen Li; Fangping Liu (Molecular & Cellular Toxicology, 2021)